Implementasi Tugas dan Fungsi Panitera dalam Sistem Administrasi Perkara Pidana di Pengadilan Militer III-12 Surabaya - Uswatun Hasanah; Rusmilawati Windari (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
This research discusses the implementation of the duties and functions of the Registrar at the Military Court III - 12 Surabaya in the criminal case administration system. The purpose of this research is to evaluate the suitability of the Registrar's duties with applicable regulations, namely PERMA No. 7 of 2015 and Law no. 31 of 1997 concerning Military Justice. The method used is empirical juridical with a qualitative approach, which includes interviews and document analysis. The research results show that the Registrar has three main tasks: carrying out case administration, assisting judges in trials, and implementing decisions. Even though it complies with regulations, there are challenges in carrying out tasks, such as manual processes, limited register books, and problems with coordination and understanding the law. This research recommends improving administrative facilities and systems, training for human resources, and periodic evaluations to increase the effectiveness of criminal case administration at the III-12 Surabaya Military Court.